2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9175811
|View full text |Cite
|
Sign up to set email alerts
|

Muscles Cooperation Analysis Using Akaike Information Criteria for Anterior Cruciate Ligament Injury Prevention

Abstract: In this paper, we propose the analysis method for finding out the similarity of the muscle force patterns to mine the risk factor of the anterior cruciate ligament (ACL) injury. Akaike information criteria (AIC) under the assumption of the auto-regression model is adapted to analyze the similarities of muscle force patterns in time-series. The difference of AIC values between 2 muscles is considered to be the distance between 2 muscle force patterns and the dexterity of the maneuver is expected to be discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There have been many epidemiological studies of injuries in badminton athletes [2][3][4][5][6][7][10][11][12]. Experts believe that analyzing badminton injuries will help coaches and athletes to reduce the risk of injury to badminton athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many epidemiological studies of injuries in badminton athletes [2][3][4][5][6][7][10][11][12]. Experts believe that analyzing badminton injuries will help coaches and athletes to reduce the risk of injury to badminton athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several clinical analyses of injuries revealed that badminton injuries generally occur in the lower limb, with more than 58% of cases in that area [11]. Interestingly, ACL injuries are particularly common, making up 37% of all injuries, according to Uchiyama, et al [12].…”
Section: Introductionmentioning
confidence: 99%